Educational Programme for Pregnant Women About Zika Virus Infection in Benha City (International Journal of Studies in Nursing, 2018)
Background: Zika virus has potential to cause a pandemic so it becomes a major public health concern worldwide. Even if its effect on adults is commonly mild, Zika creates expressive risks for developing fetuses of infected women during pregnancy. The present study is quasi-experimental study aiming to examine the impact of Zika Virus Infection educational program for pregnant women on their knowledge, attitude and practice before and after applying for the program. Setting: The study was performed at antenatal clinics in maternal and child health care center at Benha city from the beginning of August 2015 until October2015. The study sample consisted of105 pregnant women simple randomly included in the study. The data was collected through a structured Interviewing questionnaire for the mother to assess the level of women's knowledge attitude and reported practice related to ZIK virus were assessed before and after the program. The results revealed that there was a significant improvement in the nurses' knowledge score about Meaning, causative agent, Vaccine, symptoms, complications, investigations, and management of Zika virus; moreover, there was an improvement in total reported practices about Zika tends to rise. Conclusion: There was an improvement in knowledge, attitude, and practice of the participant's post-program. Based on the results of the study recommended that: Health education to pregnant women about the Zika virus should be included in the antenatal health education program as well as the need for additional public health messaging to avoid it.